Finite element modeling of anatomical constitutional types of the lumbar spine and pelvis (Roussouly) for study of the biomechanical aspects - Shulga Alexey E.; Ulyanov Vladimir Yu.; Rozhkova Yuliya Yu.; Shuvalov Stanislav D. (Гений oртопедии)
Introduction Sagittal morphotypes graded by Roussouly are characterized by specific biomechanics of the spinopelvic alignment (SPA) that can be investigated using the finite element (FE) modeling. The objective was to design three-dimensional realistic models simulating anatomical and constitutional types LPA and evaluate deformity and strength of the models under compression. Materal and methods Lateral standing spondylograms of the skull, pelvis and upper third of the femur were produced for volunteers (n = 169) who agreed to participate in the study. Radiographs were interpreted with Surgimap 2.3.2.1.) and computed tomography (CT) of the SPA was performed for individuals (n = 5) with average sagittal parameters for each of the five Roussouly morphotypes (I, II, III, IIIA, IV). The CT findings were used to simulate (SolidWorks) five parametric finite element models of normal morphotypes of SPA and examine the deformity and strength. Results The highest von Mises stresses under compression were measured in the bodies and intervertebral discs (IVD) ThX–LI (2.961 MPa), posterior supporting structures LIV–SI (2.515 Mpa) with type I model; vertebral bodies and IVD of the thoracic and lumbar spine, mainly at the ThXII–LI (3.082 MPa) and LIV– LV (3.120 Mpa) levels with type II model; anterior aspects of the bodies and IVD ThXI–LII, posterior thirds of the bodies, pedicles and facet joints LI–SI (1.720 Mpa) with type III model; the bodies and intervertebral discs of the ThIX–LII vertebrae (1.811 MPa), posterior supporting structures of the LI–SI vertebrae (1.650 Mpa) with type IIIA model; in the spinous processes and articular portion of the arches of the LI–SI vertebrae (3.232 MPa) with type IV model. Discussion The lateral configuration of the SPA has a key effect on the segmental distribution of gravitational force and determines the specificity of the sagittal biomechanics of the spine, its resistance to dynamic loads and tendency to various degenerative pathologies. Conclusion Types III and IIIA were the most biomechanically balanced types, hypolordotic form (types I and II) was associated with overloaded anterior vertebral structures including intervertebral disc protrusion (IDP) and overloaded posterior supporting structures in case of hyperlordosis (type IV).